2020
DOI: 10.1177/0300060520949767
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the pyroptosis signaling pathway in a sepsis-associated encephalopathy cell model

Abstract: Objectives The inhibition of pyroptosis has a protective effect in sepsis-associated encephalopathy (SAE). However, the mechanisms underlying pyroptosis in SAE remain to be elucidated. Methods Here, we investigated the effects of the caspase inhibitors, Belnacasan (Beln) and Wedelolactone (Wede), on an induced model of SAE in P12 cells, using immunofluorescence, ELISA, western blotting, and flow cytometry. Results The cell viability decreased, IL-1β and IL-18 secretion increased, and the levels of the caspase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[53,[63][64][65][66][67][68][69][70][71][72]. Pyroptosis has been proved to be closely related to sepsis-induced organ damage, but whether inhibiting pyroptosis could be a possible therapy tactic for the brain in sepsis is starved for more evidence [73,74]. In this study, we focus on exploring the candidate molecules or pathways that could regulate pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[53,[63][64][65][66][67][68][69][70][71][72]. Pyroptosis has been proved to be closely related to sepsis-induced organ damage, but whether inhibiting pyroptosis could be a possible therapy tactic for the brain in sepsis is starved for more evidence [73,74]. In this study, we focus on exploring the candidate molecules or pathways that could regulate pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the noncanonical pathway, cytosolic LPS is sensed by casepase-4/5/ 11, which are in turn activated and cleave GSDMD into GSDMD-NT. In sepsis, both pathways can be activated (134). The NOD-like receptor and pyrin domain containing 3 (NLRP3) is one of the most-explored inflammasomes involved in the canonical pathway (135).…”
Section: Neuronal Lossmentioning
confidence: 99%
“…Then, GSDMD-NT becomes a ring-like structure and forms holes in the cell membrane, which causes the production of IL-1β and IL-18, and leads to cell lysis. The canonical signaling pathway plays a potential role in the pathogenesis of SAE, and the inhibition of pyroptosis may be a useful therapeutic target for SAE ( 95 , 96 ).…”
Section: The Immune Response Of Cns In the Development Of Saementioning
confidence: 99%
“…With this regard, expressions of NLRP3, GSDMD-NT, and cleaved caspase-1 were augmented in the brain of septic mice, and the upregulation of NLRP3, caspase-1, and gasdermin-D in the hippocampus resulted in the cognitive deficits in the mice model of SAE by inducing pyroptosis ( 99 ). Recently, we found that sestrin 2 improved the outcome of sepsis by decreasing the NLRP3/caspase-1-dependent pyroptosis, and it was closely related to the protein kinase RNA (PER)-like ER kinase (PERK)-activating transcription factor (ATF)4-C/EBP homologous protein (CHOP) pathway ( 95 ). Moreover, Lei et al ( 100 ) explored the nexus between autophagy and pyroptosis in mice with SAE, and the results showed that both autophagy and pyroptosis were involved in the development of SAE in mice, and pannexin-1 decreased the occurrence of pyroptosis by autophagy.…”
Section: The Immune Response Of Cns In the Development Of Saementioning
confidence: 99%
See 1 more Smart Citation